THE EVOLUTIONARY DIALECTIC OF NATURE: A STUDY IN RALPH WALDO EMERSON'S THE SNOW-STORM - Salloom , Aida Thamer; Jawad, Enas Jaafar (Journal of Higher Education and Academic Advancement, 2024)
The forefather of Transcendentalism or the American Romanticism that pervaded the political and literary scene of America in the mid-19th century, Ralph Waldo Emerson is a prolific and distinguished American essayist, lecturer, philosopher and poet. He strived to create a new American spirit, a new cultural basis and a heroic narrative that maintain an elevation of the American self. Though simple in their language and poetic diction, Emerson's essays and poems reflect his philosophical and thoughtful ideas in a dignified and melodious system. The study attempts to explore Emerson's appreciation to the dynamic, creative and evolutionary power of nature, advocating a unity between man and nature to help develop his intuition and regain his divine knowledge. Having a qualitative method, the study presents a reverent consideration to Emerson's essay Nature as a basic theoretical part for his concepts of the power of nature. A practical exemplification of Transcendentalism and the connectedness between nature and the human experience is thoroughly presented in the analysis of Emerson's poem "The Snow-Storm